2020
DOI: 10.1007/s10029-019-02119-z
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo evaluation of a reinforced ovine biologic: a comparative study to available hernia mesh repair materials

Abstract: Purpose Two innovative reinforced biologic materials were studied in a non-human primate hernia repair model. The test articles, which combine layers of ovine decellularized extracellular matrix with minimal amounts of synthetic polymer, were evaluated for their biologic performance as measured by inflammatory response, healing kinetics, integration, and remodeling into functional host tissue. For comparison, seven clinically used biologic and synthetic meshes were also studied. Methods Animals were implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…Ovine forestomach matrix (OFM) is a dECM derived from the rumen of sheep, specially the propria submucosa, and has been shown to contain a number of ECM proteins including 24 different collagens, proteoglycans, including perlecan and decorin (DCN), cytokines and growth factors [ 22 , 23 ]. In vivo studies have demonstrated that OFM is anti-inflammatory [ 24 ], stimulates angiogenesis [ 25 ] and is remodeled over time [ 26 ]. Clinically, OFM has found a range of applications in soft tissue repair, including wound healing [ 27 33 ], reconstructive surgery [ 34 ], and abdominal wall repair [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ovine forestomach matrix (OFM) is a dECM derived from the rumen of sheep, specially the propria submucosa, and has been shown to contain a number of ECM proteins including 24 different collagens, proteoglycans, including perlecan and decorin (DCN), cytokines and growth factors [ 22 , 23 ]. In vivo studies have demonstrated that OFM is anti-inflammatory [ 24 ], stimulates angiogenesis [ 25 ] and is remodeled over time [ 26 ]. Clinically, OFM has found a range of applications in soft tissue repair, including wound healing [ 27 33 ], reconstructive surgery [ 34 ], and abdominal wall repair [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,23 The OFM bioscaffold has been shown to inhibit MMPs and neutrophil elastase, 16 and undergoes constructive remodelling in vivo, consistent with an antiinflammatory response. 15,18,24 Wide excision of HS-affected tissue leaves a significant full-thickness defect which, left to heal via secondary intention, may result in significant scar contracture and loss of functional status of the affected area. Dermal substitutes have been part of the reconstructive ladder for many years, although their use in HS reconstruction is limited relative to their widespread use in applications such as burns, necrotising fasciitis, trauma and wounds.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additionally, structural studies demonstrate that OFM retains a native matrix architecture similar to the ECM of healthy human skin. 9 This structural and compositional mimicry of healthy tissue ECM facilitates a range of biological properties, for example OFM to inhibit a range of tissue proteases, 21 and stimulate cell migration, infiltration, proliferation and differentiation, 7,8,22 and the recruitment of mesenchymal stromal cells. 10 In comparison to a synthetic dermal matrix, such as reconstituted collagen/ glycosaminoglycan, the OFM graft is expected to impart greater biological functionality, attributed to a preserved ECM structure and composition.…”
Section: Discussionmentioning
confidence: 99%